The window, the street, the ink, the scribble... César Vallejo against the reality of his time - Merino, Antonio (2021)
Vallejo is the sum and result of his actions and his work. Write knowing the commitment that comes with a challenge. He does not improvise; he does not feel the need or the foolishness of the careerists who wield criticism with the ideological arguments of a certain caste of the empowered.